Nonviral Gene Therapy - Li, S.; Ma, Z. (Current Gene Therapy, 2001)
The last 10 years have seen substantial progress in the development and application of nonviral vectors in gene therapy. Several novel nonviral methods have been developed that approach viruses with respect to transfection efficiency. A variety of nonviral delivery systems that can be used for gene therapy in different clinical settings are also available. In this review article, we will detail all of the major nonviral vectors that are currently used in gene therapy while highlighting some recent developments, particularly the progress towards the understanding of the cellular and in vivo barriers in gene transfer. Recent advancement in achieving sustained and regulated gene expression will also be addressed. Finally, this review will briefly cover targeted gene repair using nonviral delivery systems. Their impact in gene therapy will also be discussed.
Keywords: Single chain hydrocaron-anchored lipids